Blindness in a Sri Lankan woman with bilateral breast lumps: a case report. (December 2015) - Bataduwaarachchi, Vipula; Galappaththi, Rukshani; Tissera, Nirmali
Abstract Background Granulomatosis with polyangiitis is a rare multisystemic autoimmune disorder predominantly affecting the upper and lower respiratory tracts and the kidneys, and rarely affecting other organ systems. Tuberculosis can mimic the presentation of granulomatosis with polyangiitis, and both can occur simultaneously in the same patient. Here we report what we believe to be the first case of concurrent granulomatous breast lesions and hemorrhagic retinal angiopathy in a Sri Lankan woman with refractory granulomatosis with polyangiitis complicated by probable tuberculosis. Case presentation A 48-year-old Sri Lankan Moorish woman presented with a 6-month history of ulcerating bilateral breast lumps, a 3-month history of non-healing painful ulcers on the palate, and sudden bilateral painless loss of vision. Retinoscopy confirmed left-sided retinal hemorrhages and bilateral panuveitis. An examination of her respiratory system showed bilateral coarse crepitations. Histologic examination of the palatal and breast lesions showed chronic granulomatous inflammation. Her levels of immune markers were elevated but her renal function was normal. Chest radiography showed bilateral mid-zone and lower-zone infiltrates with cavitation and small pleural effusions. Her serum proteinase 3 anti-neutrophil cytoplasmic antibody titer and the level of adenosine deaminase in her pleural fluid were significantly elevated. She was diagnosed with generalized granulomatosis with polyangiitis complicated with probable pulmonary tuberculosis, and was started on methylprednisolone and cyclophosphamide pulse therapy with anti-tuberculous treatment. She later developed cerebral vasculitis, indicating refractory disease, and was treated with second-line rituximab with excellent response. Conclusion Proteinase 3 anti-neutrophil cytoplasmic antibody may be a valuable diagnostic marker in patients with atypical symptoms of granulomatosis with polyangiitis or in the presence of probable tuberculosis. Retinal vascular angiopathy needs to be diagnosed and treated early to prevent the development of complete blindness. Concomitant cytotoxic and anti-tuberculous treatments may be safe and effective in patients with simultaneous refractory disease with probable tuberculosis.